Neorotalia omanensis and Operculina musawaensis from the Sultanate of Oman - Al-Sayigh, Abdul Razak Siddiq (Sultan Qaboos University Journal for Science [SQUJS], 2013)
Two new species of larger benthic foraminifera, Neorotalia omanensis n. sp. and Operculina musawaensis n. sp. are described and illustrated from the eastern Oman Mountains. N. omanensis n. sp. occurs in the Musawa Formation in association with the planktonic foraminifera Morozovella edgari and Truncarotaloides topilensis indicating an early to middle Eocene age (P10-P13). Operculina musawaensis n. sp. occurs in the Abat Formation in association with the planktonic foraminifera Acarinina esnaensis and A. soldadensis indicating an early Eocene age (P6). This is the first known record showing the presence of genus Neorotalia in the Middle East. Representatives of the larger foraminiferal genus Linderina sp. are also described and illustrated from the Musawa Formation and compared with the published Linderina species in the surrounding countries.